Potential of Lactic Acid Bacteria Isolated From Different Forages as Silage Inoculants for Improving Fermentation Quality and Aerobic Stability - Puntillo, Melisa; Gaggiotti, Mónica; Oteiza, Juan Martín; Binetti, Ana; Massera, Ariel; Vinderola, Gabriel (Frontiers in Microbiology, 2020)
We aimed at isolating lactic acid bacteria (LAB) from different plant materials to study their crossed fermentation capacity in silos and to find strains able to confer enhanced aerobic stability to silage. 129 LAB isolates were obtained from lucerne (alfalfa), maize, sorghum, ryegrass, rice, barley, canola, Gatton panic, Melilotus albus, soy, white clover, wheat, sunflower, oat and moha. Four Lactobacillus plantarum strains (isolated from oat, lucerne, sorghum or maize) were selected for their growth capacity. Identity (16S sequencing) and diversity (RAPD-PCR) were confirmed. Fermentative capacity (inoculated at 104, 105, 106, 107 CFU/g) was studied in maize silage and their cross-fermentation capacity was assessed in oat, lucerne, sorghum and maize. Heterofermentative strains with the highest acetic acid production capacity conferred higher aerobic stability to maize silages. Regardless the source of isolation, L. plantarum strains, inoculated at a rate of 106 CFU/g, were effective to produce silage from different plant materials. From more than 100 isolates obtained, the application of a succession of experiments allowed us to narrow down the number of potential candidates of silage inoculants to two strains. Based on the studies made, L. plantarum LpM15 and L. fermentum LfM1 showed potential to be used as inoculants, however further studies are needed to determine their performance when inoculated together. The former because it positively influenced different quality parameters in oat, lucerne, sorghum and maize silage, and the latter because of its capacity to confer enhanced aerobic stability to maize silage. The rest of the strains constitute a valuable collection of autochthonous strains that will be further studied in the future for new applications in animal or human foods.